2017
DOI: 10.5152/turkjorthod.2016.011
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Cone Beam Computed Tomography in Orthodontics: A Review

Abstract: Cone Beam Computed Tomography (CBCT) is being extensively used in orthodontics for diagnostic and treatment planning, especially in complex clinical conditions. The objective of this study was to review the English language literature for current applications and trends of CBCT in orthodontic diagnosis and treatment. Several electronic databases were searched with the primary words: "orthodontics and radiography" and "cone beam computed tomography" or "CBCT. " Abstracts that appeared to fulfill our inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…When evaluating the tooth regions, three regions were defined: the incisor, premolar, and molar regions. Teeth 11,12,13,21,22,23,31,32,33,41,42,and 43 were in the incisor region, teeth 14, 15, 24, 25, 34, 35, 44, and 45 were in the premolar region, and teeth 16, 17, 26, 27, 36, 37, 46, and 47 were in the molar region (the third molar teeth were not included). The mean age value was taken as a reference when defining age groups.…”
Section: Cbct Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating the tooth regions, three regions were defined: the incisor, premolar, and molar regions. Teeth 11,12,13,21,22,23,31,32,33,41,42,and 43 were in the incisor region, teeth 14, 15, 24, 25, 34, 35, 44, and 45 were in the premolar region, and teeth 16, 17, 26, 27, 36, 37, 46, and 47 were in the molar region (the third molar teeth were not included). The mean age value was taken as a reference when defining age groups.…”
Section: Cbct Measurementsmentioning
confidence: 99%
“…In addition, the role of CBCT in oral, dental, and maxillofacial surgery, orthodontics, airway assessment, temporomandibular joint disorders, endodontics, and periodontology appears to be important [10,11]. Measurements and evaluations performed with CBCT enable the determination of the length of the edentulous area, alveolar bone thickness, and crest height [12,13]. One of the advantages of CBCT for orthodontic purposes relates to its ability to provide images of the alveolar bone surrounding the teeth buccally and lingually.…”
Section: Introductionmentioning
confidence: 99%
“…Despite robust justification of CBCT in selected cases, some authors found insignificant differences in treatment planning decisions when CBCT was used versus conventional imaging [98], and others have stated that, even though CBCT may alter treatment planning, it does not necessarily improve or change orthodontic treatment outcome [99,100,101]. It is difficult to assess the exact value of CBCT with regards to changing the orthodontic treatment outcome because the evidence on CBCT efficacy and diagnostic value is not obtained from randomized controlled trials, but rather mostly from observational studies or studies with variable hierarchy of evidence [102,103].…”
Section: Justifying the Use Of Cbct In Orthodontics According To Ementioning
confidence: 99%